A new species and first record of Androdeloscia (Oniscidea: Philosciidae) from Colombia. (2nd January 2017) - López-Orozco, Carlos Mario; Carpio-Díaz, Yesenia M.; Navas Suárez, Gabriel Rodolfo; Campos-Filho, Ivanklin Soares
ABSTRACT: The genus Androdeloscia includes 24 Neotropical species distributed in Central and South America. This study describes the new species Androdeloscia colombiana sp. nov. from El Chorro, Soplaviento, and from the Botanical Garden Guillermo Piñeres, Turbaco, Bolívar, Colombia. This is the first record of the genus in Colombia. http://zoobank.org/urn:lsid:zoobank.org:pub:AEA56E26-1F6D-4DDA-BA02-D73DE9FAD198